Quality of life of women with lymphedema after surgery for breast cancer - Marislei Sanches Panobianco; Natalia Campacci; Letícia Meda Vendrusculo Fangel; Maria Antonieta Spinoso Prado; Ana Maria de Almeida; Thais de Oliveira Gozzo (Rev Rene)
This study evaluated the quality of life of 20 women with post-mastectomy lymphedema due to breast cancer, using the Flanagan’s Adapted Quality of Life Scale (1) and the Visual Analogue Scale (2), with data collection from July to December 2009 in the countryside of the state of São Paulo. It was observed a lower quality of life concerning participation in recreational and work activities, and better quality of life was related to relationship with friends; listening to music, reading, watching TV and going to the movies. Cronbach's alpha of Scale 1 was 0.86 and the average of Scale 2 was 6.26. Overall, the scales showed satisfactory results of quality of life, but low values showed factors that must be worked out, such as participation in sports, work and learning activities. Thus, lymphedema interferes with the quality of life, indicating a need for early intervention in order to help women achieve better quality of life.